The Pulwama-Balakot Crisis: A Strategic Assessment - Dr. Mansoor Ahmed; Maimuna Ashraf (CISS Insight Journal, 2019)
The Pulwama crisis has again brought to light the peculiar nature of crisis instability, and revalidated the stability-instability paradox in South Asia. While it reinforced the efficacy of Pakistan’s overall deterrence posture vis-à-vis India, this crisis also exposed India as a “trigger-happy” nuclear armed-state, while Pakistan’s crisis behavior demonstrated resolve, restraint and responsibility. The U.S. monopoly as an effective third-party broker and crisis manager was replaced by multilateral efforts to prevent escalation. However, given the growing power differential between India and Pakistan, India is likely to continue to explore ways and means to conduct kinetic action against Pakistan, while the latter will have to maintain an effective defence against the full-spectrum of evolving threats.